Treatment decision-making and care among older adults with kidney failure: protocol for a multicentre, prospective observational cohort study with nested substudies and linked qualitative research (the Elderly Advanced CKD Programme) - Martin Gallagher; Vasi Naganathan; Gian Luca Di Tanna; Celine Foote; Angela Makris; Chris Gianacas; Nicholas A Gray; Isaac Yeboah Addo; Amanda Siriwardana; Chenlei Kelly Li; Kenneth Yong; Yachna Mehta; et al. (BMJ Open, 2022)
Introduction Shared treatment decision-making and planning of care are fundamental in advanced chronic kidney disease (CKD) management. There are limited data on several key outcomes for the elderly population including survival, quality of life, symptom burden, changes in physical functioning and experienced burden of healthcare. Patients, caregivers and clinicians consequently face significant uncertainty when making life-impacting treatment decisions. The Elderly Advanced CKD Programme includes quantitative and qualitative studies to better address challenges in treatment decision-making and planning of care among this increasingly prevalent elderly cohort.Methods and analysis The primary component is OUTcomes of Older patients with Kidney failure (OUTLOOK), a multicentre prospective observational cohort study that will enrol 800 patients ≥75 years with kidney failure (estimated glomerular filtration rate ≤15 mL/min/1.73 m2) across a minimum of six sites in Australia. Patients entered are in the decision-making phase or have recently made a decision on preferred treatment (dialysis, conservative kidney management or undecided). Patients will be prospectively followed until death or a maximum of 4 years, with the primary outcome being survival. Secondary outcomes are receipt of short-term acute dialysis, receipt of long-term maintenance dialysis, changes in biochemistry and end-of-life care characteristics. Data will be used to formulate a risk prediction tool applicable for use in the decision-making phase. The nested substudies Treatment modalities for the InfirM ElderLY with end stage kidney disease (TIMELY) and Caregivers of The InfirM ElderLY with end stage kidney disease (Co-TIMELY) will longitudinally assess quality of life, symptom burden and caregiver burden among 150 patients and 100 caregivers, respectively. CONsumer views of Treatment options for Elderly patieNts with kiDney failure (CONTEND) is an additional qualitative study that will enrol a minimum of 20 patients and 20 caregivers to explore experiences of treatment decision-making and care.Ethics and dissemination Ethics approval was obtained through Sydney Local Health District Human Research Ethics Committee (2019/ETH07718, 2020/ETH02226, 2021/ETH01020, 2019/ETH07783). OUTLOOK is approved to have waiver of individual patient consent. TIMELY, Co-TIMELY and CONTEND participants will provide written informed consent. Final results will be disseminated through peer-reviewed journals and presented at scientific meetings.